Effectiveness of Combining Lidocaine and Ropivacaine on the Duration of Analgesia and Anesthesia of an Infraclavicular Brachial Plexus Block - Steensbæk MT; Temberg JL; Yousef S; Pisljagic S; Steen-Hansen C; Nørskov AK; Lange KHW; Rothe C; Lundstrøm LH (Local and Regional Anesthesia)
Mathias T Steensbæk,1 Jens L Temberg,1 Sina Yousef,1 Sanja Pisljagic,1 Christian Steen-Hansen,1 Anders K Nørskov,1,2 Kai HW Lange,1,2 Christian Rothe,1 Lars H Lundstrøm1,2 1Department of Anesthesia and Intensive Care, Copenhagen University Hospital - North Zealand, Hillerød, Denmark; 2Department of Clinical Medicine, University of Copenhagen, Copenhagen, DenmarkCorrespondence: Mathias T Steensbæk, Department of Anesthesia and Intensive Care, Copenhagen University Hospital - North Zealand, Dyrehavevej 29, 3400, Hillerød, Denmark, Email mathias.therkel.steensbaek.01@regionh.dkBackground: Combining local anesthetics for peripheral nerve blocks may change block characteristics, resulting in altered onset and block duration. We aimed to investigate the block characteristics of an infraclavicular brachial plexus block regarding block duration, pain after block cessation, and patient satisfaction by using a combination of lidocaine-epinephrine and ropivacaine.Methods: In this retrospective cohort study, 103 patients undergoing ambulatory hand or wrist surgery received an infraclavicular brachial plexus block with either a combination of ropivacaine 5 mg/mL combined with lidocaine 20 mg/mL and epinephrine 5 μg/mL (COMBI group) or only ropivacaine 5 mg/mL (ROPI group). The primary outcome was “Total block duration”. Secondary outcomes were “Time until block begins to subside”, “Pain after complete block cessation (Numerical Rating Scale 0– 10)”, and “Patient experience of nerve block”. All outcomes were patient-reported. Multivariable regression analyses were used to adjust for predefined potential confounders.Results: “Total block duration” (mean ± SD) was 655± 215 minutes in the COMBI group and 961± 195 in the ROPI group; mean difference of 309 minutes; P< 0.001. “Time until block begins to subside” was 396± 120 minutes in the COMBI group and 642± 214 minutes in the ROPI group; P< 0.001. The median “Pain after block cessation” on a Numeric rank scale (NRS) was 5.0 (IQR 3.0– 8.0) in the COMBI group and 6.0 (IQR 4.0– 7.0) in the ROPI group; P=0.80. In the COMBI group, 60% were satisfied with block quality versus 38% in the ROPI group; P=0.042. Multivariable adjusted analyses confirmed the results regarding block duration and pain after block cessation but not satisfaction.Conclusion: Combining lidocaine-epinephrine and ropivacaine reduced the duration of analgesia by approximately 5 hours. Pain after block cessation was moderately high in both groups.Keywords: infraclavicular, nerve, block, ropivacaine, lidocaine, duration